1999
DOI: 10.1159/000054122
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients with Venous Thromboembolism and Cancer Be Treated Differently?

Abstract: Patients with malignant disease constitute a significant subgroup among patients with venous thromboembolism. Current results suggest that cancer patients are not only at an increased risk for thromboembolic events, particularly during chemotherapy treatment or after surgery, they also have an increased risk for bleeding complications while receiving oral anticoagulant treatment. The exact incidences of venous thromboembolic complications for the various types of cancer, however, are not well determined. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The high failure rate of long-term oral anticoagulant treatment in patients with venous thromboembolism and cancer suggests that alternative treatments should be evaluated, and it has been suggested that long-term lowmolecular-weight heparin use may be superior to oral anticoagulants in these patients. 2,17 The results of the present study support this hypothesis, suggesting that a full dose of enoxaparin is at least as effective as and may be safer than warfarin for the long-term treatment of venous thromboembolism in cancer patients. Since initial anticoagulant treatment was short and did not differ between the 2 groups, the results may not be explained by differences in the initial prestudy treatment or by the site and extension of the underlying cancer, which were also well balanced between the 2 groups.…”
Section: Commentsupporting
confidence: 77%
See 1 more Smart Citation
“…The high failure rate of long-term oral anticoagulant treatment in patients with venous thromboembolism and cancer suggests that alternative treatments should be evaluated, and it has been suggested that long-term lowmolecular-weight heparin use may be superior to oral anticoagulants in these patients. 2,17 The results of the present study support this hypothesis, suggesting that a full dose of enoxaparin is at least as effective as and may be safer than warfarin for the long-term treatment of venous thromboembolism in cancer patients. Since initial anticoagulant treatment was short and did not differ between the 2 groups, the results may not be explained by differences in the initial prestudy treatment or by the site and extension of the underlying cancer, which were also well balanced between the 2 groups.…”
Section: Commentsupporting
confidence: 77%
“…is a frequent complication of active malignancy and has been repeatedly identified as a marker of poor outcome in patients with cancer. [1][2][3] Patients with cancer and venous thromboembolism have a 3-fold lower survival at 1 year than patients with cancer who do not have venous thromboembolism. 3 The increased mortality rate observed in cancer patients with venous thromboembolism may result from a more advanced cancer state 3 but can also be related to venous thromboembolism itself, which is difficult to treat in these patients.…”
Section: Arch Internmentioning
confidence: 99%
“…Cancer patients are at an increased risk of developing venous thromboembolism (VTE) as compared with the general population [1,2]. Cancer itself can induce a hypercoagulable state by pressure on veins, damage of vessel walls and by direct or indirect activation of the coagulation system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have demonstrated that LMWH reduces the risk of recurrent VTE, decreases the risk of major bleeds associated with UFH, and may offer a survival benefit in patients with cancer (Dolovich, Ginsberg, Douketis, Holbrook, & Cheah, 2000;Leizorovicz, 1996;Lensing, Prins, Davidson, & Hirsh, 1995;Smorenburg, Hutten, & Prins, 1999). Based on these findings, the ACCP Consensus Conference recommended the use of LMWH over UFH (Hyers et al, 2001).…”
Section: Treatment Of Thrombosismentioning
confidence: 99%